Distinguishing semantic control and phonological control and their role in aphasic deficits: A task switching investigation. (13th August 2022) - McCall, Joshua; van der Stelt, Candace M.; DeMarco, Andrew; Dickens, J. Vivian; Dvorak, Elizabeth; Lacey, Elizabeth; Snider, Sarah; Friedman, Rhonda; Turkeltaub, Peter
Abstract: People use cognitive control across many contexts in daily life, yet it remains unclear how cognitive control is used in contexts involving language. Distinguishing language-specific cognitive control components may be critical to understanding aphasia, which can co-occur with cognitive control deficits. For example, deficits in control of semantic representations (i.e., semantic control), are thought to contribute to semantic deficits in aphasia. Conversely, little is known about control of phonological representations (i.e., phonological control) in aphasia. We developed a switching task to investigate semantic and phonological control in 32 left hemisphere stroke survivors with aphasia and 37 matched controls. We found that phonological and semantic control were related, but dissociate in the presence of switching demands. People with aphasia exhibited group-wise impairment at phonological control, although individual impairments were subtle except in one case. Several individuals with aphasia exhibited frank semantic control impairments, and these individuals had relative deficits on other semantic tasks. The present findings distinguish semantic control from phonological control, and confirm that semantic control impairments contribute to semantic deficits in aphasia.